2010
DOI: 10.1016/j.yebeh.2010.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder caused by the misattribution of seizure-related experiential responses

Abstract: Patients with temporal lobe seizures sometimes experience what John Hughlings Jackson described as "dreamy states" during seizure onset. These phenomena may be characterized by a re-experiencing of past events, feelings of familiarity (déjà vu), and hallucinations. In previous reports, patients have been aware of the illusory nature of their experiences. Here, however, the case of a patient with a documented 37-year history of temporal lobe epilepsy who is not aware is described. Fifteen years ago, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, a handful of recent case reports document the occurrence of more debilitating forms of déjà experiences. For example, Cohen et al [ 80 ] report a man with a long history of complex TLE, who after experiencing a concussion following a seizure, began to encounter vivid intrusions of traumatic events. However, investigation of his history and questioning his family revealed that although aspects of these events did occur, the memories he was recalling were not veridical.…”
Section: Clinical Remarksmentioning
confidence: 99%
“…However, a handful of recent case reports document the occurrence of more debilitating forms of déjà experiences. For example, Cohen et al [ 80 ] report a man with a long history of complex TLE, who after experiencing a concussion following a seizure, began to encounter vivid intrusions of traumatic events. However, investigation of his history and questioning his family revealed that although aspects of these events did occur, the memories he was recalling were not veridical.…”
Section: Clinical Remarksmentioning
confidence: 99%
“…The third – Regardless of the anatomical proximity, this interaction could also be related to the psychological reaction to stress. It could be argued that the epileptic activity might have an affective negative bias ( Clark, 1920 ; Gunn and Baram, 2017 ; Lang et al, 2018 ), and that this bias can lead to increased stress and anxiety thus triggering PTSD related anxiety ( Cohen et al, 2010 ) forming a vicious cycle. In this regard, PTSD related stress might lead to a reactive seizure and vice versa ( Greig and Betts, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, as we had only limited collateral information regarding the actual sexual assault, it could be claimed that what seemed to be an enactment of the assault as observed in the new seizures type was a déjà vu experience or false reminiscences as describe by Hughlings Jackson ( Hughlings-Jackson, 1880 ). Such false reminiscences can even lead in rare cases to a PTSD-like clinical picture ( Stewart and Bartucci, 1986 ; Cohen et al, 2010 ). Second, we limited our analysis to the fear circuitry of PTSD and did not assess other potential circuits involved in PTSD, such as emotional regulation and context processing ( Sheynin and Liberzon, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations